Tuning compatibility and water uptake by protein charge modification in melt-polymerizable protein-based thermosets. Issue 4 (24th January 2022) - Andersen, Emil; Chan, Wui Yarn; Av-Ron, Sarah; Sureka, Hursh V.; Olsen, Bradley D.
Abstract : The effects of charge state on water uptake and mechanical properties of thermoset protein-based copolymers were investigated. Superneutralization was shown to reduce the material's mechanical property variation with humidity. Abstract : Suppressing the influence of humidity in protein-based materials is central to their use in a variety of applications. It is believed that protein charge plays a key role in water uptake. Therefore, in this work, whey protein was neutralized, supercharged, and superneutralized to examine the effects of protein modification on moisture absorption in protein copolymers. The charge-modified proteins were formulated into thermoset elastomers through a three-step process: methacrylation, complexation with various surfactants, and co-polymerization with n -butyl acrylate. Compatibility of the protein and hydrophobic acrylate monomer can be tuned through changes in surfactant type, ratio between surfactant and protein, and protein charge modification. Using benzalkonium chloride as the surfactant compatibilizer, elastomers with the various modified proteins were prepared using a melt polymerization approach. Acetylation and esterification of whey protein, which neutralize charged functional groups, resulted in the reduction of the proteins' water uptake relative to unmodified whey. Once incoporated into elastomers, all copolymers regardless of protein modifications have similar moisture contents. However, elastomers with superneutralized proteins demonstrated a lowered mechanical dependence on humidity, presented as a smaller change in elongation at break and tensile strength compared to a copolymer based on non-charge modified whey.